Analisis Butir Soal Ujian Semester Ganjil Mata Pelajaran Bahasa Indonesia Kelas VIII - Harisa Putri, Winda; Mukhlis, Muhammad (UIR Press, 2023)
One of the problems in making questions is achieving a balanced proposition. To achieve a balanced proposition, both easy, medium and difficult questions must be represented properly. In this study, the authors used a quantitative approach and descriptive method. Based on an analysis of the odd semester exam questions for class VIII Indonesian at SMP Negeri 3 Pekanbaru for the 2018/2019 academic year, the authors conclude that the difficulty level index aspect of the questions is categorized as easy, because the highest percentage of questions are in the easy category, namely 34 questions (68%). However, when viewed from the aspect of item discrimination, it is categorized as inappropriate because the highest percentage is in the ineligible category, namely 41 items (82%). In terms of the effectiveness of the distractor, as a whole, seen from the students' answers, it is categorized as having a distractor that does not function properly. Therefore, these items cannot be used and must be discarded.